LC–HRMS-Guided Network Pharmacology Reveals PARP1-Targeting Phytochemicals from Zanthoxylum acanthopodium with Anti-Melanoma Activity - Linda Chiuman; Dewi Purnama; Chrismis Novalinda Ginting; Ermi Girsang; Hariyadi Dharmawan Syahputra; Iksen Iksen (Journal of Multidisciplinary Applied Natural Science, 2026)
Melanoma is an aggressive skin cancer with frequent therapeutic resistance, highlighting the need for multi-target discovery strategies. In this study, an integrative workflow combining LC–HRMS metabolite profiling, network pharmacology, structure-based modeling, and phenotypic evaluation was applied to explore the anti-melanoma potential of Zanthoxylum acanthopodium ethanol extract (ZAE). LC–HRMS analysis followed by ADMET-guided screening prioritized 12 candidate metabolites representing diverse structural classes. Integration of transcriptomic datasets, GeneCards targets, and compound-based predictions identified eight consensus genes, with poly(ADP-ribose) polymerase 1 (PARP1) emerging as the top hub within the protein–protein interaction network. Functional enrichment analysis highlighted pathways associated with DNA damage response and apoptosis-related signaling. Molecular docking against the PARP1 catalytic domain suggested favorable binding profiles for several prioritized metabolites, and molecular dynamics simulation supported stable interaction behavior under dynamic conditions. In vitro anticancer evaluation in A375 melanoma cells demonstrated concentration-dependent reduction in viability (IC₅₀ = 128.03 ± 10.17 μg/mL, 24 h) accompanied by apoptosis-associated nuclear alterations. Overall, this study provides a chemically informed, systems-level framework indicating that ZAE-derived metabolites may influence melanoma cell survival through PARP1-centered stress and apoptosis signaling, offering a foundation for future target validation and structure-guided optimization.